2018
DOI: 10.1155/2018/1281657
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Postoperative Cognitive Dysfunction and Delirium in Noncardiac Surgery Using MRI: A Systematic Review

Abstract: Surgical patients are at high risk of developing postoperative cognitive dysfunction (POCD) and postoperative delirium (POD). POCD and POD are associated with increased morbidity and mortality and worsening functional outcomes leading to severe socioeconomic consequences for the patient and the society in general. Magnetic resonance imaging (MRI) offers a unique opportunity to study the anatomy and function of the brain. MRI thus plays an important role in elucidating the neuronal component of POCD and POD. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 66 publications
(108 reference statements)
1
24
2
4
Order By: Relevance
“…Furthermore, unlike the other groups, as a subtype of POD, hyperactive POD was not found in the DEX 400 µg group (consistent with a previous report) (Carrasco et al, 2016). It was suggested that POD may be associated with postoperative pathological changes in the white matter, while a reduction in thalamic and hippocampal volumes contributed to POCD (Huang et al, 2018). An age-related cognitive decline often follows variations in regional brain volume, serotonin receptor binding, accumulation of neurofibrillary tangles, and concentrations of various brain metabolites (Kadota et al, 2001;Fotenos et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, unlike the other groups, as a subtype of POD, hyperactive POD was not found in the DEX 400 µg group (consistent with a previous report) (Carrasco et al, 2016). It was suggested that POD may be associated with postoperative pathological changes in the white matter, while a reduction in thalamic and hippocampal volumes contributed to POCD (Huang et al, 2018). An age-related cognitive decline often follows variations in regional brain volume, serotonin receptor binding, accumulation of neurofibrillary tangles, and concentrations of various brain metabolites (Kadota et al, 2001;Fotenos et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…In literature, POD was diagnosed within the rst seven days or in a longer period (23,24). In our study, there were 8 patients (2.6%) who were diagnosed early (the rst 3 postoperative days).…”
Section: Discussionmentioning
confidence: 55%
“…26 The Minnesota Multiphasic Personality Inventory (MMPI) is currently one of the most commonly used tests in the world using the questionnaire test method consisting of a total of 566 questions in the form of selfreporting. 27 Further, there are some methods, such as nerve electrophysiological examination, 28 transcranial Doppler ultrasound imaging (TCD), 29 and magnetic resonance imaging (MRI) 7 that are also performed for evaluating changes between POCD and non-POCD patients. However, a standard assessment method is urgently needed to investigate POCD and its risk factors.…”
Section: Diagnosis Of Pocdmentioning
confidence: 99%
“…At certain times, POCD might be confused with delirium, which presents acute and fluctuating disturbances of consciousness that usually occur 24 to 72 h after surgery, whereas POCD is a more permanent problem related to a change in cognitive function. 7 Hip arthroplasty remains one of the most commonly used and successful contemporary surgical interventions performed in older adults. 8 The number of hip arthroplasty patients has increased dramatically over the last decade, and this trend is expected to continue as the population ages.…”
Section: Introductionmentioning
confidence: 99%